Differences in the Effects of Neck Calliet Exercise and Myofascial Release on Reducing Pain in Muscle Neck Pain Sufferers - Yani, Fitri; Wulan, Wulan Octari; Setiawan, Danur (Universitas Muhammadiyah Surakarta, 2024)
Introduction: Neck pain is an uncomfortable sensation in the neck area. Neck pain is one of the most prevalent diseases in the world. The impact that occurs will be experiencing stiffness in the neck, limited movement of the neck, and neck pain resulting in a decrease in functional neck Objective: To determine whether there is a difference in the effect of the neck called workout and myofascial release on pain reduction in patients with upper trapezius muscle neck pain. To determine whether there is a difference in the effect of neck exercise and myofascial release on reducing pain in patients with neck pain of the upper trapezius muscle. Methods: This study is experimental with a pre-test and post-test two-group design. A total of 16 respondents were determined using the sample random sampling technique. This study was divided into 2 groups of 8 respondents each: the first treatment group with neck called exercises and the second with myofascial release e. The exercise was carried out for 2 weeks with a frequency of exercise 3 times a week. The measuring tool used is the Visual analogue scale (VAS), normality test using the Shapiro-Will test. Homogeneity test using Lavene's test, hypothesis testing I and II using paired sample t-test, and hypothesis testing III using independent sample t-test. Results: There is no significant difference in the effect of neck exercise and myofascial release on reducing pain in patients with neck pain of the upper trapezius muscle. Conclusion: Both Neck Calliet Exercise and Myofascial Release effectively reduce pain in upper trapezius muscle neck pain. However, there is no significant difference between the two in pain reduction effectiveness.